The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0102-311x2005000500023
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes e padrões de utilização da bicicleta e acidentes de trânsito sofridos por ciclistas trabalhadores da cidade de Pelotas, Rio Grande do Sul, Brasil

Abstract: A population-based cross-sectional study was conducted in Pelotas, southern Brazil, focusing on the determinants and patterns of bicycle use as a mode of commuting by workers. Accidents during commuting and use of safety equipment were also studied. The sample included 1,705 workers (> 15 years of age) living in the urban area of Pelotas and using various modes of transportation during commuting. Crude and adjusted analyses were performed using Poisson regression, taking the design effect into account. Prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 16 publications
(18 reference statements)
3
29
0
12
Order By: Relevance
“…The result was similar to that observed in the worker population living in the urban area of Pelotas, where only 17.2% of the participants use the bicycle as a means of commuting to work (Bacchieri et al, 2005).…”
Section: Introductionsupporting
confidence: 86%
“…The result was similar to that observed in the worker population living in the urban area of Pelotas, where only 17.2% of the participants use the bicycle as a means of commuting to work (Bacchieri et al, 2005).…”
Section: Introductionsupporting
confidence: 86%
“…Finally, no information was collected about the commuting distance (e.g. distance and destination), which may be an important confounding factor in the analysis; however, this factor was considered in a different study that showed similar results 22 . Therefore, it is concluded that Curitiba has less bicycling than European cities but rates similar to those of locations in North and Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from low and middle-income countries is scarce. Economic and social aspects, such as a larger low income population 9,22 , social norms that do not value the bicycle as a means of transportation, the aggressive behavior of drivers 19 and a lack of facilities for bicycling 23 may present challenges to the promotion of bicycling in these countries. To identify the correlates of bicycling will help to improve interventions, programs and policies aiming at promoting the adoption of bicycling 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence, few studies investigated leisure and transportation bicycling in Brazil 3,4 . Population-based studies conducted in Pelotas-RS, Brazil, observed that 17% of workers use the bicycle to commute to work 5 and 13% of adults use it in their leisure time 4 . By contrast, bicycling is substantially higher in high-income countries, between 22 and 32% to commute to work 6,7 , 41% to commute to college 8 , and 26% in leisure time.…”
Section: Introductionmentioning
confidence: 99%
“…Studies point out that lack of time and interest, distance to destination, physical discomfort, and low practicality as a mode of transportation are among the most reported barriers to bicycling in adults [7][8][9] . Brazilian studies demonstrated that individual aspects (male sex, lower education and socioeconomic status -SES) are associated with bicycling to commute to work 4,5 . In leisure time, living with a partner was associated with bicycling 4 .…”
Section: Introductionmentioning
confidence: 99%